Kotmāi Wat Kāsā : tonchabap Wat Kāsā, ʻAmph̄œ M̄æ Čhan, Chīang Rāi (Nangs̄ư pariwat čhāk khamphī bailān. Chut tamnān m̄ưang læ kotmāi Lānnā, 1983)
Governing criminal procedure based on customary law of Thailand.